COPTIC CANOPIAN DOMES IN ARCHITECTURE AND ART IN EGYPT - Emad Adel Ibrahim (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2019)
The Coptic Canopian domes considers Egyptian invent, trance fare to all civilizations, and show in medieval ages with major development [1]. The Coptic architect executed this architectural element to accentuate element at the bottom of the dome. It refers to the importance of this place and gives it a kind of sanctity and reverence. So the architect carried out the element of the Coptic Canopian dome on the altar and baptistery and the chair of the Bishop and the Ambon only. Inside the dome the artist depicted the heavenly scenesto confirm the concept and purpose of make dome over the altar or baptistery. The architect and artist wanted to feel the priest who stand in heaven the angels hear his prayers. So the Coptic Canopian element symbolizes the sky.